Expressive Laboratory for parents in Neonatal Intensive Care Unit - Rocco Agostino; Anna Mancini; Annamaria Trovato (Hygeia Press di Corridori Marinella, 2013)
Introduction: The admittance of a baby in NICU is a chocking and stressful experience for parents that need support to comprehend and accept circumstances and help to start the relation with their baby. Expressive Laboratory (EL) is a counseling activity that offers parents the possibility to explore their emotional experience by participating with other parents in meetings with a counselor and a psychologist. Materials and method: The EL includes a set of nine meetings, planned in three moments: pre-contact, contact and post-contact, each meeting is focusing on a particular theme and at the end parents fill out an anonymous feedback form where they can show their appreciation of the activities performed, the benefit obtained and the emotions experienced. Results: From May 2009 to September 2010 seven sets of meetings were organized in which 142 parents participated and they filled out 286 feedback forms. The main results from this descriptive study concerned feelings as: sharing the experience, ability to express oneself, finding resources. Some comments go beyond the activities of EL. Conclusions: The major benefits of EL reported by the parents are the sharing of the experience; not to feel lonely during the hospital stay. The experience to share allows a full understanding of the stories, promoting the creation of a support net that lasts even after the discharge of the baby with self-aid groups.